Intention to use of fintech products and services among youngsters: The application of technology acceptance model (TAM) - Farah Syahirah Ishak; Muhamad Syafiq Azman; Siti Nor Munirah Abdul Mutalib; Siti Nor Nasuha Awang (2022)
Financial Technology or famous known as “Fintech” is an innovative financial service that emerged in tandem with the new technologies and advancement. The Islamic Banking and Finance researchers and students have recently started to explore the emerging industry of fintech with reference to Islamic Banking and Finance. Thus, the purpose of this study is to investigate the intention to use of fintech products and services among youngsters based on the application of Technology Acceptance Model (TAM). Quantitative method has been used which based on articles, journals and any other related materials. The data is collected from 357 youngsters using questionnaire through Google Form. The result of this study will show the measure level, examine the relationship and analyze the significant influence of perceived ease of use, perceived usefulness, and service trust on intention to use of Fintech’s products and service among youngsters. However, this study has potential limitations that occur during collection of the date which are limitation in the area of study, lacking time, and lacking fund and those limitations can be improved in the future.